Efforts to Improve Integrated Science Learning Achievement Material Inheritance Through Application of Discovery Learning Learning Models in Class IX C Students of MTsN 9 Ngawi - Chudlori, Mochammad (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2019)
This research is a class action research. The place of this research is in class IX C MTsN Ngawi. The research period is the odd semester of the 2018/2019 academic year starting from July to September 2018. The subjects of this study are students of class IX C MTsN 9 Ngawi. The data collection techniques used in this study are observation or observation and tests to determine student learning achievement. The data analysis technique used in this study is a quantitative descriptive. The results showed that the application of the Discovery Learning learning model can improve IPA learning achievement Integrated Inheritance Material The nature of students in the subject matter calculates the arithmetic sequence and sequence principal. This can be seen in the value of the average learning achievement of students experiencing an increase in the cycle I, II and cycle III. Before the action is held, the average value of students is 65.53. After the first cycle of action is taken to be 66.00 and after the improvement of actions in the second cycle is held, the average value increases to 71.00. These results continued to increase in the third cycle to 79.25. While based on the percentage of students 'mastery learning, the results of the percentage of students' mastery learning from the initial condition of 50% (10 people) increased to 65% (13 people) and increased again in the second cycle to 73% (15 people). After repairs were held, there was an increase again in cycle III to 88% (18 people). The application of the Discovery Learning learning model can improve student learning activities. This increase can be seen from each cycle that starts from the activity of students in the initial condition of 50% (10 people) to 65% (13 people) in the first cycle and then increases again in the second cycle to 73% (15 people), and after being held improvements to deficiencies in cycles I and II, the results of student learning activeness in cycle III increased to 88% (18 people).